Globalization and Distorted Development: In Search of a System Perspective for Sustainability - Menanteau, Dario (Journal of Sociocybernetics, 2013)
The controversial relationship between globalization and social development still dominates the intellectual and socio-political debate of our days.  The 21st century has evolved, so far, without an agreement between those who promise prosperity and opportunities in an expanded and international world market and those who claim that globalization, as it has been carried on today,  is a negative force for peace, equity, and social development.While the most visible effects of globalization include the internationalization of the world economy, the expansion of markets, and a growing interconnectedness among countries, the process also carries major consequences for social development. In fact, the most serious consequence, especially in Third World countries, is the inability of national governments to invest in programs of social welfare.  Policies of national development are being reduced as the role of the state is being diminished. Today, social stratification has become international while inequality remains global.As demonstrated by today’s financial and economic international crisis, current patterns of globalization reaffirm a growing interdependence of the world economy, modern technology, and communications. The same process, however, carries little or no change in old conditions of international stratification, global inequality, and insufficient efforts for social development.This paper examines three main issues pertinent to globalization:(1) First, the notion that globalization is a new phenomenon and a different paradigm is highly questionable.  Less developed countries have had long histories of dependent relationships and vulnerability to external political and economic powers.  (2) Globalization has produced conditions of “distorted development” characterized by economic growth without social development. (3) More functional and sustainable relationships between globalization and social development are explored and discussed. The paper reviews sociocybernetic principles of the “Viable System” suggested by Stafford Beer.